Strategi Penguatan Potensi Desa dengan Karakteristik Degradasi Lahan di Desa Panggung Duwet, Kabupaten Blitar - Wahyu Santoso; Rossyda Priyadharshini; Maroeto Maroeto (Institut Pertanian Bogor, 2020)
The purpose of the Student Study Service Programs are 1) Synergizing socio-cultural local wisdom with community economic characteristics for preventing degradation of agricultural land through the KKN program. 2) Formulate strategies to increase the potential of villages towards developed and independent villages. The method of collection is done in two kinds, namely primary data by means of surveys, questionnaires and interviews with the village secretary, village apparatus, community leaders, farmer groups and residents around of Panggung Duwet Village’s related to the KKN program, and secondary data in the form of well-documented data such as Blitar Regency in the Numbers, Kademangan District in the Numbers as well as the Report on the Implementation of the Village Administration and/or the Report on the Accountability of the Panggung Duwet Village’s in 2018. The data analysis method was conducted using the social intervention and SWOT analysis approaches. The results of the implementation of the Student Study Service Programs in Panggungduwet Village, Kademangan District are implemented into a work program that is greening, processing waste into organic fertilizer and crafts, processing food commodities such as corn silk syrup, cassava donuts and cassava chips. Analysis of the village situation shown still has weaknesses, namely lack of water supply, especially in the dry season, especially agriculture in line with the opportunities that exist, namely seeking organic fertilizer by utilizing waste and wood sawdust crafts for sale so that the potential is expected to be a catalyst for village development to become advanced and independent. The existence of the Student Study Service Programs can leave a good impression so that the community is willing to begin to change the bad behavior of agricultural land management that ignores the rules of conservation and increased knowledge and skills of processed waste and food processed in order to improve the economic welfare of the community.